2021
DOI: 10.1038/s41564-021-00918-8
|View full text |Cite
|
Sign up to set email alerts
|

A standardized archaeal taxonomy for the Genome Taxonomy Database

Abstract: An increasing wealth of genomic data from cultured and uncultured microorganisms provides the opportunity to develop a systematic taxonomy based on evolutionary relationships. Here we propose a standardized archaeal taxonomy, as part of the Genome Taxonomy Database (GTDB), derived from a 122 concatenated protein phylogeny that resolves polyphyletic groups and normalizes ranks based on relative evolutionary divergence (RED). The resulting archaeal taxonomy is stable under a range of phylogenetic variables, incl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
250
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 257 publications
(264 citation statements)
references
References 81 publications
13
250
0
1
Order By: Relevance
“…Annotation of the phylogenetic tree was accomplished with the online tool "Interactive Tree Of Life (iTol) v4" (https://itol.embl.de; accessed on 15 January 2021) [34]. Taxonomic classifications are according to the Genome Taxonomy Database (GTDB) (https://gtdb.ecogenomic.org; accessed on 15 January 2021) and to NCBI Taxonomy (https://www.ncbi.nlm.nih.gov/ taxonomy; accessed on 15 January 2021) [31,[35][36][37].…”
Section: Data Sample and Haloarchaeal Phylogenetic Tree Constructingmentioning
confidence: 99%
See 1 more Smart Citation
“…Annotation of the phylogenetic tree was accomplished with the online tool "Interactive Tree Of Life (iTol) v4" (https://itol.embl.de; accessed on 15 January 2021) [34]. Taxonomic classifications are according to the Genome Taxonomy Database (GTDB) (https://gtdb.ecogenomic.org; accessed on 15 January 2021) and to NCBI Taxonomy (https://www.ncbi.nlm.nih.gov/ taxonomy; accessed on 15 January 2021) [31,[35][36][37].…”
Section: Data Sample and Haloarchaeal Phylogenetic Tree Constructingmentioning
confidence: 99%
“…From the analysis of this classification, it can be assumed that the number of available genomes from Halobacteria class is suitable and significant for this research. There are representatives from all described families in literature, and from the great part of the genera [35][36][37]. Nevertheless, due to the low number of species classified in each genus, it was concluded that genera classification is not suitable for a deeper study.…”
Section: Search For Denitrification Genes and Proteinsmentioning
confidence: 99%
“…The numbers of ANME varies in different ecosystems, but usually ranges from 10 5 to 10 7 cell/g and accounts for 1-20% of the total microbial population [10,23]. These microorganisms, so far unavailable in pure culture, belong to the phylum Euryarchaeota (or to the phylum "Halobacteriota" according to GTDB [25] and are represented by three phylogenetic groups: ANME-1 with subgroups a and b (Candidatus Methanophagales), ANME-2 with subgroups a, b, c, d, and ANME-3. They are not monophyletic: ANME-2 and ANME-3 belong to Methanosarcinales while ANME-1 has a separate deep phylogenetic lineage [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…Metagenome information not only opens an avenue to explore the diversity and metabolic potentials, but also lays a foundation for phylogenomic studies of the largely uncultured archaeal species, which has resulted in a rapid growth of the archaeal phylogenetic tree with a number of new phyla, classes and orders ( 22 24 ). Very recently, Parks et al ( 25 , 26 ) have developed a Genome Taxonomy Database (GTDB), the first comprehensive prokaryote taxonomy based on phylogenomic analysis, which inferred phylogenetic trees from the concatenation of single-copy vertically inherited genes, and provided higher resolution than those based on single gene. The GTDB has also recorded amazingly diverse archaea, and more than 40 phyla are proposed, however, with the majority encompassing only a few or even no cultured species ( 26 ).…”
Section: Introductionmentioning
confidence: 99%
“…Very recently, Parks et al ( 25 , 26 ) have developed a Genome Taxonomy Database (GTDB), the first comprehensive prokaryote taxonomy based on phylogenomic analysis, which inferred phylogenetic trees from the concatenation of single-copy vertically inherited genes, and provided higher resolution than those based on single gene. The GTDB has also recorded amazingly diverse archaea, and more than 40 phyla are proposed, however, with the majority encompassing only a few or even no cultured species ( 26 ).…”
Section: Introductionmentioning
confidence: 99%